(untitled) (Croatian Sociological Review, 2025)
The paper discusses how Srđan Lelas (1939-2003), one of the first Croatian philosophers of science, tried to derive a specific version of scientific antirealism from evolutionary considerations. While scientific realists believe that scientific theories refer to the objectively existing world and provide its true descriptions, antirealists believe that claims about the objective existence of at least some parts of that world are not neutral with respect to the theory and that instead of the truth of scientific theories, it is better to talk about their theoretical usefulness and predictive ability. Lelas formulates the antirealist perspective as a thesis about the “non-instrumentality” of the cognitive subject (the subject’s share as a specific “cognitive tool” cannot be removed from cognitive achievement) and believes to find support for this in “modern Darwinism” of R. Lewontin, according to which the organism is one of the central and ineliminable factors of evolution and evolutionary explanations. The paper examines Lelas’s drawing of a parallel between antirealism and the idea of the organism as an ineliminable factor of evolution. It turns out that this parallel entails several problems that Lelas did not reflect on: the problem of “genetic fallacy”, the problem of inconsistency with the standard view of “biological functions” in the philosophy of biology, and the problem of not taking into account theories of the units of natural selection that reject the centrality of organism. In conclusion, the central considerations of the paper are recapitulated and a rough assessment of Lelas’s philosophy of science is given.